Successful Percutaneous Coronary Intervention in Chronic Total Occlusion after Coronary Perforation - Luis A. Areiza; Juan F. Rodriguez (Case Reports in Cardiology)
Coronary chronic total occlusions are challenging lesions with high rates of complications related to percutaneous intervention. We describe a successful angioplasty in a patient with a recent coronary perforation, using multiple techniques, such as stick and swap with Stingray, subintimal transcatheter withdrawal, and investment.